Pengaruh Moisture Content pada Insinerator Municipal Solid Waste - Putra, Gede Suba Ratya; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract The high amount of rainfall in Indonesia causes Municipal Solid Waste (MSW) to have a high moisture content. One of the efforts that can be made to process MSW is through the thermal process of Incineration which is a solid fuel reduction process with high temperatures using an incinerator. This study aims to analysed the effect of moisture content in MSW on the temperature profile and combustion efficiency in a dual chamber incinerator. The MSW used comes from an organic mixture of dry leaves, paper, cardboard, coconut shell and plastic, the composition is arranged to be homogeneous for each variation and then the moisture content is adjusted by drying treatment to suit the variations used, namely 10% moisture content (MC) for the 1st Variation, 20% MC for 2nd variation, and 30% MC for 3rd variation. Tests were carried out by inserting MSW through the fuel feeder in the incinerator and then burning at a control temperature of 900 ° C and supplying blower air to the combustion chamber at 10m/s. The results of this experimental research show that the 10% moisture content variation has the highest peak combustion temperature with temperatures of 1020°C in chamber1 and 1130°C in chamber2 and better combustion efficiency is also obtained by the 10% moisture content variation with an efficiency value of 92.67%. This indicates that the reduction of moisture content in MSW can increase the combustion temperature in the Dual Chamber Incinerator, and increase the combustion efficiency. Keywords: Municipal Solid Waste, Incinerator, Moisture Content